Studying the Influence of Mg Content on the Microstructure and Associated Localized Corrosion Behavior of Zn-Mg PVD Coatings Using SVET-TLI. Issue 11 (1st January 2019) - Bolton, Rebecca; Dunlop, Thomas; Sullivan, James; Searle, Justin; Heinrich, Helge; Westerwaal, Ruud; Boelsma, Christiaan; Williams, Geraint
Abstract : Physical vapour deposited (PVD) zinc and zinc-magnesium coatings are compared to commercial galvanized zinc and zinc-magnesium-aluminum coatings in terms of bare metal corrosion when immersed in chloride-containing solution. A scanning vibrating electrode technique has been augmented to capture photographic images, in-situ, which complement the spatially and temporally resolved electrochemical data by providing visual evidence of corrosion events and their subsequent stabilization or propagation over the surface. Hot dip galvanized zinc coatings demonstrate heterogeneous localized corrosion behavior, contrary to the general corrosion of the PVD pure zinc layer. The PVD coating containing 4 wt% magnesium has a discrete microstructure much finer than the structure of hot dip zinc-magnesium-aluminum coatings, which results in smaller and more abundant anodic features. Increasing the magnesium content in PVD zinc-magnesium to 10 wt% coatings increases the relative size of the anodic events and reduces the number observed accordingly. A further increase in magnesium content to 20 wt% sees a reduction in anode size and evidence of de-activation during the experiment. A clear correlation between magnesium content and the intensity of characteristic staining on the PVD coatings is also observed.